Seimbangkan Game Online dengan Game Offline di Era Revolusi Industri 4.0 - Husniah Ramadhani Pulungan (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2019)
This article aims to strike a balance between online games that have some negative impacts and offline games (which are paired with the term sports or games) in the era of the industrial revolution 4.0. The method used is descriptive qualitative with a case study because the source of the data is from the uti-utian of the Angkola tribe which originates from a written document titled